2016
DOI: 10.1530/edm-16-0092
|View full text |Cite
|
Sign up to set email alerts
|

Active postoperative acromegaly: sustained remission after discontinuation of somatostatin analogues

Abstract: SummaryIn patients with active acromegaly after pituitary surgery, somatostatin analogues are effective in controlling the disease and can even be curative in some cases. After treatment discontinuation, the likelihood of disease recurrence is high. However, a small subset of patients remains symptom-free after discontinuation, with normalized growth hormone (GH) and insulin-like growth factor (IGF1) levels. The characteristics of patients most likely to achieve sustained remission after treatment discontinuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…If SSA therapy is discontinued, recurrence will be present in 56% of cases after 12-16 weeks of treatment withdrawal [34]. However, numerous cases and series of cases of prolonged remission and biochemical control of acromegaly after SSA withdrawal have been reported [35]. Remission is more likely in patients with a lower GH and IGF-1 level prior to treatment, absence of adenoma in magnetic resonance image (MRI) scans, with a long-term treatment and an adequate response to low doses.…”
Section: Somatotropinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…If SSA therapy is discontinued, recurrence will be present in 56% of cases after 12-16 weeks of treatment withdrawal [34]. However, numerous cases and series of cases of prolonged remission and biochemical control of acromegaly after SSA withdrawal have been reported [35]. Remission is more likely in patients with a lower GH and IGF-1 level prior to treatment, absence of adenoma in magnetic resonance image (MRI) scans, with a long-term treatment and an adequate response to low doses.…”
Section: Somatotropinomasmentioning
confidence: 99%
“…Remission is more likely in patients with a lower GH and IGF-1 level prior to treatment, absence of adenoma in magnetic resonance image (MRI) scans, with a long-term treatment and an adequate response to low doses. The rate of patients with prolonged remission (>12 months) varies highly from 16 to 41.7%, probably due to differences in inclusion criteria among the studies [35]. An expert consensus of acromegaly, published in 2014, recommends to consider treatment withdrawal in patients with well-controlled acromegaly, despite a decrease in SSA administration to the minimally effective dose and an increased dose interval (up to every 3 months).…”
Section: Somatotropinomasmentioning
confidence: 99%
“…In this group, 4/6 patients were already in remission at the end of the previous study of Ronchi et al (updated median follow up time of 132 months, IQR 111-153). At the end of that previous study, 5 (18.5%) patients resulted in remission after a median follow up time of 24 months (IQR 21-36 months) but 1 patient had a relapse 30 months after withdrawal so that therapy with SAs (OC) was re-initiated. Pituitary imaging remained stable after drug withdrawal in all these 6 patients.…”
Section: Relationship Between Long-term Remission and Clinical Parametersmentioning
confidence: 94%
“…Some previous papers demonstrated that a sustained clinical inactivity and stabilization of GH/IGF-1 levels is possible in patients with acromegaly, even after the discontinuation of SAs treatment. However, most of them were isolated case reports or they included only a small number of selected patients with a "transient" disease remission after a relatively short period of drug removal (mostly 6-24 months) [15][16][17][18][19]. Moreover, our group previously observed, in a multicentre study, the possibility of a successful withdrawal of SAs in 5 of 27 good responders after a median period of 24 months [20].…”
Section: Introductionmentioning
confidence: 99%
“…The latter finding makes SSA a suitable pre-operative medication for decreasing perioperative morbidity and tumor volume, as well as improving surgical outcome [52]. The effect on remission rates and recurrence (15% to 84%) after SSA discontinuation is highly variable [53], although complete remission of 4 years after discontinuation was reported in a case [53]. As one of the examples of SSA intolerance, SSA-associated deterioration in glucose metabolism via inhibition insulin secretion has recently been reported, which can be predicted by plasma glucose 120 minutes post-oral glucose tolerance test (OGTT) [35].…”
Section: Current Treatment Approachesmentioning
confidence: 99%